Housing access challenges for young people: A holistic analysis from real estate professionals - Gutiérrez-Aragón, Óscar; Fondevila-Gascón, Joan-Francesc; Alcalde-González, Hugo; Gómez-Gómez, Daniel (RAN - Revista Academia & Negocios, 2026)
Purpose: To understand the perception of real estate professionals in Spain regarding the problem of housing access among young adults in Spain, in order to determine its causes and identify solutions. Methodology: A qualitative analysis was conducted using data from semi-structured interviews with long-standing real estate professionals in the province of Barcelona. Results: A pessimistic perception of access to housing among young people was found, with little likelihood of improvement in the medium term. Furthermore, it is estimated that the marketing strategies used for this target group are neither adapted to their actual situation nor focused on their real needs. Implications: The solution to the problem must come from public-private cooperation and the real estate sector´s improvement of marketing strategies and employee training to serve this population group. Originality: This study provides the viewpoint sale-purchase agents to address a problem that has traditionally been approached from the unidimensional perspective of supply and demand.